Effect of ventilation of vessel and different media on maturation and germination rate of sago embryos - Rasyada, . A. Rahman @ Rahim (Universiti Malaysia Sarawak, (UNIMAS), 2008)
Metroxylon sagu is a significantly important economic Metroxylon species for starch production purposes. In this study, effects of ventilation capacity of the vessels and different media constituents on maturation and germination of sago somatic embryos were investigated. The main objectives of this project were to study the effects of ventilation and variation of the selected media constituents in culture medium formulation on maturation and germination of sago somatic embryos. Four main studies were conducted. The effects of culture ventilation were investigated by physical method which used different types of cover for culture vessels. Second and third studies were on concentration variability of sorbitol as osmoticum and silver nitrate as ethylene inhibitor respectively. The fourth study was on the effect of activated charcoal and PVP in media incorporated with and without ABA. Sago somatic embryos were cultured on enrichment media and incubated in the dark condition at 24C. Analysis of variance showed that at two months after initiation of the experiment and first sub-culture, the difference in the mean number of mature and germinated sago embryos developed in the ventilated and un-ventilated vessels was highly significant. Sorbitol at 25 g/L is the optimum concentration for the highest maturation rate of sago somatic embryos. compared to other tested levels. As compared to media without AgNO, media with incorporation of silver nitrate at2.5, 8.S and 13 mg/L gave poorer result on maturation of embryos. Besides, the addition of ABA in low concentration (0.005 mg/L) into culture medium containing activated charcoal without PVP and vice versa, have been induced the maturation of somatic embryos. Statistical analyses were used for these studies are t-test, one-way ANOVA and Nested Design.